Microsoft SQL Server 2008 step by step - Hotek, Mike (Step by step (Redmond, Wash.), 2009)
Teach yourself SQL Server 2008-one step at a time. Get the practical guidance you need to build database solutions that solve real-world business problems. Learn to integrate SQL Server data in your applications, write queries, develop reports, and employ powerful business intelligence systems. Discover how to: Install and work with core components and toolsCreate tables and index structuresManipulate and retrieve dataSecure, manage, back up, and recover databasesApply tuning plus optimization techniques to generate high.